2010
DOI: 10.1186/1475-2867-10-8
|View full text |Cite
|
Sign up to set email alerts
|

A cancer derived mutation in the Retinoblastoma gene with a distinct defect for LXCXE dependent interactions

Abstract: BackgroundThe interaction between viral oncoproteins such as Simian virus 40 TAg, adenovirus E1A, and human papilloma virus E7, and the retinoblastoma protein (pRB) occurs through a well characterized peptide sequence, LXCXE, on the viral protein and a well conserved groove in the pocket domain of pRB. Cellular proteins, such as histone deacetylases, also use this mechanism to interact with the retinoblastoma protein to repress transcription at cell cycle regulated genes. For these reasons this region of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Thus, specific functional deficits of RB, such as those arising in the LXCXE-binding motif, could be relevant to tumor suppression or regulation of disease progression through distinct mechanisms. Consistent with this concept, the LXCXE binding pocket is targeted by viral oncoproteins, coordinates interaction with multiple proteins of biological significance, and is mutated in cancer (Henley et al, 2010; Morris and Dyson, 2001). …”
Section: Introductionmentioning
confidence: 85%
“…Thus, specific functional deficits of RB, such as those arising in the LXCXE-binding motif, could be relevant to tumor suppression or regulation of disease progression through distinct mechanisms. Consistent with this concept, the LXCXE binding pocket is targeted by viral oncoproteins, coordinates interaction with multiple proteins of biological significance, and is mutated in cancer (Henley et al, 2010; Morris and Dyson, 2001). …”
Section: Introductionmentioning
confidence: 85%
“…Given that it has been reported that threonine 821/threonine 826 phosphorylation disrupts Rb binding to LXCXE motif-containing proteins (Knudsen and Wang, 1996 ; Dick and Rubin, 2013), we examined whether the function of cytoplasmic Rb is achieved through its interaction with LXCXE motif-containing proteins. We introduced mCherry-HA-NES Rb lacking exon 22 (Rb Δexon 22), which is known to be an LXCXE-binding deficient mutant (Henley et al, 2010), into HSMMs and found that the inhibitory effect of NES Rb Δexon 22 on sarcomeric organization was less effective as compared to NES Rb-expressing HSMMs (Figure 7A).
10.7554/eLife.01228.011Figure 7.The function of cytoplasmic Rb is rendered through its interaction with LXCXE motif-containing proteins.( A ) Sarcomeric structure is not disordered in NES Rb Δexon 22-expressing HSMMs.
…”
Section: Resultsmentioning
confidence: 99%
“…Many mutations within the pRB LxCxE binding cleft disrupt the interaction of pRB with the viral oncoproteins [ 73 ]. An M704V variant of pRB retains its ability to interact with E2F3/DP1, but its ability to interact with LxCxE of SV40LTis greatly compromised [ 91 ]. A C706F variant found in small cell lung cancer is unable to interact with LxCxE motif of SV40-LT and adenovirus E1A, whereas retaining its interaction with E2F transcription factors [ 92 , 93 ].…”
Section: G 1 -S Regulation By Retinoblastomamentioning
confidence: 99%